DINAMIKA RELASI KEPALA DESA DAN BADAN PERMUSYAWARATAN DESA (STUDI KASUS DESA SURAYYA MANDIRI KECAMATAN MANDAH KABUPATEN INDRAGIRI HILIR TAHUN 2019-2021) - Saputra, Andika Saputra; ', Hasanuddin (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2026)
The enactment of Law No. 6 of 2014 concerning villages establishes that the relationship between the Village Head and the Village Consultative Body (BPD) is an important element that ideally should be collaborative, coordinative, and consultative. However, in practice, this relationship often experiences dynamics that lead to conflict, as seen in Surayya Mandiri Village, Mandah District, Indragiri Hilir Regency. This research aims to analyze the dynamics of the relationship between the Village Head and the BPD as well as conflict resolution efforts undertaken in the relationship between these two institutions. This study uses a qualitative approach with a case study design. Primary data were obtained through in-depth interviews with seven informants. Additionally, data collection was conducted through document studies. Secondary data were obtained from relevant literature and supporting documents. The findings indicate that the relationship between the Village Head and the BPD in Surayya Mandiri Village during the 2019–2021 period was conflictual. The conflict was triggered by differing interests and political backgrounds following the 2019 Simultaneous Village Head Election, where the Village Head and the BPD came from opposing factions. The sources of conflict included differing interests in managing village development resources, residual tensions from the village head election contestation, and the BPD's tendency to exceed its authority. The impact of this conflictual relationship included stagnation in village governance, delays in ratifying the Village Budget (APBDes) and Village Development Plan (RKPDes), hindered infrastructure development, and failure to distribute Direct Cash Assistance (BLT) during the Covid-19 pandemic. Conflict resolution efforts were made through conciliation and mediation. Conciliation by community leaders and mediation facilitated by the Mandah District Office yielded no results. Mediation by the Indragiri Hilir Regency Community and Village Empowerment Agency (DPMD) produced an agreement, but it was not implemented by the BPD. The conflict ultimately peaked and ended with the resignation of all BPD members and several Surayya Mandiri Village officials in 2021. Keywords: Dynamics, Conflictual Relations, Conflict Resolution